Contract Governance and the Canadian Public Sector - Ilcan, Suzan; O’Connor, Daniel; Oliver, Marcia (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
AbstractThis essay examines the changing character of public sector work in the Canadian federal public service context. It is based on an empirical examination of various forms of contractual relations currently operative within the Canadian state and on a comparative approach of other western liberal state reform initiatives. We argue that contract governance is an ongoing process involving distinct interrelations between the public and private sectors. In this context, we identify various forms of contract governance and flexibility schemes that have been enfolded and refolded into the conventional structures of governance, and unfolded into a liminal space between the state and civil society through the establishment of nonstandard work and the creation of alternative service delivery programmes.